EKSPLORASI TARI MAANTA BATANGHARI: KAJIAN TENTANG NILAI BUDAYA, PENDIDIKAN, DAN PELESTARIAN TRADISI LOKAL - Dwicahya Suryadi, Made; Nur Azizah, Siti; Nabila Azzahra, Tri; Adpariyanti, Leli; Fajarudin; Julianto, jefry; Hadid, Subron; Widiyono, Putut; Seli Safitri, Adinda; Ramadhani, Aulya; Karmila, Rosa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Indonesia's rich and diverse culture includes dance as an important element in people's lives. One of the typical dance arts is the Maanta Dance from Batanghari Regency, Jambi Province, which has a significant role in traditional wedding processions. This dance not only conveys the beauty of movement, but also cultural values such as mutual cooperation, friendship and respect for tradition. This research aims to explore the cultural values, role of education, and efforts to preserve the Maanta Dance as cultural heritage. The research uses a qualitative approach with literature study as the main method, examining various literature related to the Maanta Dance and its relevance in the context of culture, education and preserving local traditions. Data is collected from written sources, such as relevant articles, journals and books. The research results show that the Maanta Dance has deep meaning as a symbol of harmony between families, tribal unity and respect for tradition. In an educational context, this dance is effective in instilling social and cultural values in the younger generation, as well as fostering a sense of love for the country. Conservation efforts are carried out through documentation, art festivals, and integration in formal and non-formal education. Innovation in dance presentation is also an important strategy to attract the interest of the younger generation without losing traditional values. Maanta Dance plays a big role in introducing Batanghari cultural identity amidst the increasingly strong challenges of globalization.   Keywords: cultural values, maanta dance, local traditions